Apis mellifera (Hymenoptera: Apidae) as a potential Brassica napus pollinator (cv. Hyola 432) (Brassicaceae), in Southern Brazil - Rosa,AS. (2010)
Brassica napus Linnaeus is considered a self-compatible crop; however, studies show that bee foraging elevates their seed production. Considering bee food shortages during the winter season and that the canola is a winter crop, this study aimed to evaluate the foraging behaviour of Apis mellifera Linnaeus, 1758 regarding those flowers, and to verify if it presents adequate behaviour for successfully pollinating this crop in Rio Grande do Sul State. The study was carried out in a canola field, in Southern Brazil. The anthesis stages were morphologically characterised and then related to stigma receptivity and pollen grain viability. Similarly, the behaviour of A. mellifera individuals on flowers was followed, considering the number of flowers visited per plant, the amount of time spent on the flowers, touched structures, and collected resources. Floral fidelity was inferred by analysing the pollen load of bees collected on flowers. The bees visited from 1-7 flowers/plant (x = 2.02; sd = 1.16), the time spent on the flowers varied between 1-43 seconds (x = 3.29; sd = 2.36) and, when seeking nectar and pollen, they invariably touched anthers and stigmas. The pollen load presented 100% of B. napus pollen. The bees' attendance to a small number of flowers/plants, their short permanence on flowers, their contact with anthers and stigma and the integral floral constancy allows their consideration as potential B. napus pollinators.